The contribution of action research in the construction of scientific knowledge in Brazilian Production Engineering - Daniela Gibertoni; Targino de Araújo Filho; Nilton Luiz Menegon (Production)
Abstract The main subject of this article is the action research and it has as general objective to describe the construction of knowledge in this field from the uses that Brazilian Production Engineering makes of it, aiming to recognize its contributions, potentials and limits. To achieve this goal, a literature review was carried out for a subsequent contrast with the national academic researches that use action research and show its uses. Identified these similarities, a documentary research was carried out in academic papers published in the National Meeting of Production Engineering (ENEGEP) – from 1996 to 2010. The content analysis was the strategy used for data analysis and NVivo® software was used for its treatment. As a conclusion of the research, it can be stated that the use of action research in the Brazilian Production Engineering distances itself from epistemic precepts associated with it. The results of the action are more highlighted than the reflection on the mechanisms that produced it